Distinctions of Makkiyah and Madaniyyah Surahs in the Study of 'Ulum - Alwi Hanifan Fauzi; Munawir, Munawir; Ahmad Nur Hafid (al-Afkar, Journal For Islamic Studies, 2026)
This article examines the distinction between Makkiyah and Madaniyyah chapters in the study of 'Ulum al-Qur'an. The purpose of this research is to explain the differences, characteristics, benefits, and significance of the study of Makkiyah and Madaniyyah in the context of Qur'anic interpretation. The method used is library research, referring to both classical and contemporary literature. The results show that the knowledge of Makkiyah and Madaniyyah holds an essential position as a methodological tool in understanding abrogation (nasikh-mansukh), the context of revelation, and the gradual establishment of Islamic law. This study contributes to enriching the methodology of Qur'anic exegesis and provides a comprehensive understanding of the dynamics of revelation.